Supercapacitors: Elastomeric and Dynamic MnO2/CNT Core–Shell Structure Coiled Yarn Supercapacitor (Adv. Energy Mater. 5/2016). Issue 5 (March 2016) - Choi, Changsoon; Sim, Hyeon Jun; Spinks, Geoffrey M.; Lepró, Xavier; Baughman, Ray H.; Kim, Seon Jeong
Abstract : In article number 1502119, Seon Jeong Kim and co‐workers introduce reversibly deformable and highly performing solid‐state yarn supercapacitors. Mesoporous, pseudocapacitive MnO2 is electrochemically deposited on the microcoiled yarn electrodes, resulting in core(CNT)–shell(MnO2 ) structured electrodes. The coil supercapacitors can achieve high stretchability (37.5%) without the help of elastomeric substrates, minimizing the size of total supercapacitors. The yarn supercapacitors can be woven into energy textiles that can effectively power various wearable electronics in the future.